Mechanisms of Biodegradation of Toxic Organic Compounds by Microorganisms, Focusing on Alkylphenol Degradation - Chang, Young-Cheol (Research Perspectives of Microbiology and Biotechnology Vol. 8, 2024)
In this chapter, the biodegradation of various toxic compounds by microorganisms has been discussed. First, the degradation characteristics of the Bacillus sp. CYR2 strain was described. Next, the isolation methods and degradation capabilities of recently studied rhizosphere microorganisms were described. Finally, the degradation of alkylphenols in a model soil using the mold Penicillium sp. CHY-2 as an example was explained, with a particular focus on alkylphenols (APs) among the compounds discussed in this chapter. Based on 16S rRNA gene sequence and phylogenetic analysis, the isolated strain was identified as Bacillus sp. CYR2. Degradation of various toxic compounds and growth of CYR2 strain were evaluated with 2% and 4% inoculum sizes. Among the 2% and 4% inoculum sizes, bacteria showed highest growth and toxic compound degradation at 4% inoculum size. Especially, compared to 2% inoculum size, growth of the strain CYR2 at 4% inoculum size was increased by 15.3 folds with phenanthrene, 15.1 folds with 4-secondary-butylphenol, 13.6 folds with naphthalene, 9.1 folds with phenol, and 5.4 folds with 4-tertiary-butylphenol. Strain CYR2 at 4% inoculum size showed the highest removal of phenol (84±5%), followed by 4-tertiary-butylphenol (66±3%), 4-secondary-butylphenol (63±5%) and 4-nonylphenol (57±6%). Compared with 2% inoculum size, the degradation ability of strain CYR2 with 4% inoculum size was enhanced by 3.45 times with 4-tertiary-octylphenol, and 2.53 times with 4-tertiary-butylphenol. Our results indicated that the newly isolated Bacillus sp. CYR2 can be used for in situ bioremediation of phenol and APs contaminated water. The bioremediation of alkylphenols using rhizosphere microorganisms isolated from the roots of land plants was conducted. Three land plants were used to analyze the tolerance against petroleum hydrocarbons and alkylphenols. The plant Hosta undulata showed tolerance against petroleum hydrocarbons (500 mg/kg) and one of the alkylphenol, i.e., 4-tert-butylphenol (4-t-BP). Hence, thirty bacterial and thirteen fungal strains were isolated from the 4-t-BP contaminated soil collected from the roots of this plant. The biodegradation of APs was investigated using the isolated bacteria and fungi. Decrement in the APs was analyzed using high-pressure liquid chromatography (HPLC). Fungi showed higher 4-t-BP degradation than bacteria. Strain SB-4 (Penicillium pinophilum) showed 76.8%, and strain SB-7 (Trichoderma asperellum) showed 49.2% degradation of 4-t-BP under shaking and static conditions respectively. Apart from 4-t-BP, strain SB-7 degraded other alkylphenols such as 4-sec-butylphenol, 4-tert-octylphenol, and 4-nonylphenol. The major metabolites produced during alkylphenols degradation with strain SB-7 were determined using Gas chromatography linked with mass spectrometry (GC-MS). The results suggested that the plant Hosta undulata had tolerance against the toxic compounds, and the rhizosphere microorganisms isolated from the roots of this plant might be applied for the bioremediation of APs-contaminated soils. The feasibility of Penicillium sp. CHY-2 isolated from pristine Antarctic soils as a degrader of micropollutant 4-t-BP in contaminated soil containing indigenous microorganisms were evaluated for the first time. The strain CHY-2 completely degraded 4-t-BP present in the artificially contaminated soil within 3 weeks. Colony-forming unit analysis was used to observe the number of fungi and bacteria present in the soil. The viable cell count of fungi was increased from day 10 to day 21 in contaminated soil in accordance with the decrease of 4-t-BP concentration. These results suggest that 4-t-BP present in contaminated soil could be degraded by strain CHY-2.